Job Satisfaction Challenges Of Nurses In The Intensive Care Unit: A Qualitative Study - Mousazadeh S; Yektatalab S; Momennasab M; Parvizy S (Dove Medical Press, 2019)
Somayeh Mousazadeh,1 Shahrzad Yektatalab,2 Marzieh Momennasab,3 Soroor Parvizy4 1Amol Faculty of Nursing and Midwifery, Mazandaran University of Medical Science, Sari, Iran; 2Community Based Psychiatric Care Research Center, Department of Mental Health and Psychiatric Nursing, School of Nursing and Midwifery, Shiraz University of Medical Sciences, Shiraz, Iran; 3Department of Nursing, School of Nursing and Midwifery, Shiraz University of Medical Sciences, Shiraz, Iran; 4Department of Pediatric Nursing, Nursing and Midwifery Faculty, Center for Educational Research in Medical Sciences (CERMS), Iran University of Medical Sciences, Tehran, IranCorrespondence: Shahrzad YektatalabCommunity Based Psychiatric Care Research Center, Department of Mental Health and Psychiatric Nursing, School of Nursing and Midwifery, Shiraz University of Medical Sciences, Zand Blv, Namazi Square, Shiraz 71936-13119, IranTel +98 713 6474254Email Yektash@sums.ac.irBackground: Job satisfaction is an important factor in health care settings. This concept is not a single factor; rather, it is the product of factors such as the conditions and relationships that govern the workplace, the organizational system of employment, and social, cultural, and economic factors. Therefore, awareness of its related factors is important for medical staff including nurses in special units and nursing managers. The aim of the present study was to investigate job satisfaction challenges in intensive care unit (ICU) nurses.Methods: This was a qualitative study using conventional content analysis approach. This study was performed in a general ICU of Amol City, Iran. Thirteen nurses employed in the ICU were recruited until data saturation was reached. Research data were collected through interviews, a focus group and field notes. Findings were analyzed using a conventional method.Results: According to data analysis, 6 themes including “nursing education”, “organizational resources”, “management”, “multiple occupational stresses”, “professional performance” and “professional identity” were developed.Conclusion: This study provided better and clearer understanding of job satisfaction challenges of nurses working in an ICU. The findings of this research can be helpful in developing management programs for understanding the factors affecting job satisfaction of nurses and job satisfaction promotion.Keywords: job satisfaction, nurses, intensive care unit, ICU